Supporting Agriculture in the United States with the Use of Insurance Instruments (Farm Bill 2014) - Janowicz-Lomott, Marietta; Łyskawa, Krzysztof (Studia Oeconomica Posnaniensia, 2015)
Agricultural activity is carried out under conditions of risk and it is often supported by government. One kind of support is subsidized crop insurance . The Federal crop insurance system in the United States is one of the most extensive in the world. Changes in agricultural policy in 2014 reinforced the role of insurance. The article analyzes the situation of crop insurance in the United States, before t reform of 2014, and changes in the insurance system as a result of the adoption of the principles of the new agricultural policy.